A new SPRING in lipid metabolism - Hendrix, Sebastian; Zelcer, Noam (Current opinion in lipidology, 2023)
The SREBP transcription factors are master regulators of lipid homeostasis owing to their role in controlling cholesterol and fatty acid metabolism. The core machinery required to promote their trafficking and proteolytic activation has been established close to 20 years ago. In this review, we summarize the current understanding of a newly identified regulator of SREBP signaling, SPRING (formerly C12ORF49), its proposed mechanism of action, and its role in lipid metabolism. Using whole-genome functional genetic screens we, and others, have recently identified SPRING as a novel regulator of SREBP signaling. SPRING is a Golgi-resident single-pass transmembrane protein that is required for proteolytic activation of SREBPs in this compartment. Mechanistic studies identified regulation of S1P, the protease that cleaves SREBPs, and control of retrograde trafficking of the SREBP chaperone SCAP from the Golgi to the ER as processes requiring SPRING. Emerging studies suggest an important role for SPRING in regulating circulating and hepatic lipid levels in mice and potentially in humans. Current studies support the notion that SPRING is a novel component of the core SREBP-activating machinery. Additional studies are warranted to elucidate its role in cellular and systemic lipid metabolism.